Lightweight TDMA Protocol for wireless vehicular communications - Saeed, Rashid Abdelhaleem; Abakar, Ahmat; Naemat, Amran; Aris, Azrin (2010)
Wireless vehicular communications (WVC) has been identified as a key technology for intelligent transportation systems (ITS) for a few years ago. IEEE 802.11p (WAVE: wireless access in vehicular environments) is the proposed standard for physical and MAC layer of WVC devices. The standard is extended from 802.11 protocols. The main objectives of the standard are to change the frame format and increase delay spread tolerance introduced by vehicle mobility, in which the channel bandwidth is scaled from 20 MHz in 802.11a to 10 MHz in 802.11p. However, to ensure interoperability between vehicles communicate in rapidly changing environment where a packet transmission should be completed in short time-frame is a problematic issue. This poster proposes WiFi-based TDMA technique with flexible time slots and guard bands to tackle this problem. The new TDMA sublayer is compatible with the 802.11p standard to ensure the feasibility of adoption by any vendor. The simulation results present the performance analysis and validate the efficiency of the proposed method.